Examining sport tourism role in fostering social sustainability: Qatar youth perceptions - Ishac, Wadih (Frontiers in Sports and Active Living, 2024)
This study examines the evolving perceptions of youth residents in Qatar, particularly university students, regarding the social impact of hosting major sport events from 2015 to 2022. It offers crucial insights into the contribution of sport tourism in fostering social sustainability, contrasting post-event perceptions of the 2015 Handball World Championship (HWC 2015), the 2019 IAAF World Athletics Championship (IAAF 2019), and the 2022 FIFA World Cup (FIFA 2022), using a cross sectional analysis. The impact is assessed across five dimensions: community pride, enhanced community attachment, event excitement, pride in community infrastructure, and community excitement. Participants are categorized based on nationality (Qatari nationals, Arabs excluding Qataris, and Non-Arabs) to capture cultural and demographic differences. Results reveal increasingly positive perceptions across events regarding the five dimensions. Significant multivariate effects are found on the combined dependent variables for event type and nationality. The study underscores the role of hosting sporting events in advancing social sustainability and community development in Qatar. Variations among national groups indicate a need to tailor policies and strategies to foster inclusivity. The work provides valuable baseline insights to inform future hosting bids and encourage regional collaboration.